Haro and Rosario Straits - http://id.worldcat.org/fast/368731 (Great Britain. Hydrographic Service., 1872)
San Juan Boundary. Charts showing Admiralty Hydrographers opinion respecting the line of boundary as constituted by the award of the German Emperor, 21 Oct 1872. Admiralty Charts 1191 and 2689. 2.5 sea miles to one inch. Enclosed in Admiralty letter of 14 Nov 1872. Admiralty. [Haro and Rosario Straits, 1859; 1871; 1872]. At head of title: North America, west coast. Surveyed by Captn. G.H. Richards, & the Officers of H.M.S. Plumper 1858-9. Drawn for engraving by E.J. Powell. Engraved by J. & C. Walker. The shores of Juan de Fuca Strait to Admiralty Inlet from Captn. H. Kellett's survey, 1847. The east coast of Rosario Strait from Bellingham Bay to Admiralty Inlet taken from the American surveys of 1841. First published 1859 updated and corrected. Latest date on map 1871. Relief shown by hachures and spot heights; depths shown by soundings in fathoms. Includes side views of various landmarks.